Potassium Sodium Niobate Formulation And Cold Isostatic Process For Improve Piezoelectric Properties - Bahanurddin, Nor Fatin Khairah (2020)
Lead-based compounds such as Pb(Zr1-xTix)O3 (PZT) are piezoelectric ceramics that have been developed extensively for piezoelectric energy harvester (PEH) because of their outstanding electromechanical properties. However, these Pbbased materials that being used for electrical and electronic equipment become a source of waste materials that containing toxic (Pb) which can affect the environmental and human health. The high Curie temperature and good piezo and ferroelectric properties of potassium sodium niobate with common formula (KxNa1-x)NbO3 or KNN made it to be considered as a fascinating material as an alternative or to replace the existing Pb lead-based piezoelectric ceramic. However, K0.5Na0.5NbO3 (KNN) exhibits a major drawback which is difficult to produce a fully dense shape when fabricated via ordinary sintering method. It is always creating a high volatilisation of Na2CO3 and K2CO3 when exposed at high temperature which caused density start to decrease and resulting the reduction of dielectric and piezoelectric properties. In this study, the effects of Cold Isostatic Pressing (CIP) compaction pressure during shaping of pure KNN (Stage 1), Li, Sb, Ta incorperation with KNN sample (KNN-LTS) (Stage 2) and Sr2+ doped at A-site of KNN-LTS samples (Stage 3) were investigated. The samples have been prepared by solid state reaction method. Starting raw materials of K2CO3, Na2CO3 and Nb2O5 were wet mixed for 24 hour by ball mill using ZrO2 balls in ethanol medium then dried before being calcined at 850 °C for 4 hours. Pure KNN samples (Stage 1) were pressed at 95 MPa using hand press to form pellets and these pellets were re-compacted at 100, 150, 200, 250, 300 and 350 MPa, respectively using CIP and were sintered at 1080 ºC for 2 hours. XRD analysis shows that the structural phase transition from orthorhombic phase to tetragonal phase was obtained from 300 MPa as the optimum CIP pressure. This transition is responsible for the enhancement of their piezoelectric properties with optimum value obtained from sample CIPped at 300 MPa (d33 =138 pC/N, kp = 0.36, ρ = 4.17 g/cm3). The samples also show the uniform grain size (1.0-2.5 μm) and better dielectric properties (ɛr = 702 and tan δ = 0.38). Thus, KNN CIPped at 300 MPa used for further investigation in the next experimental stages. In Stage 2, KNN were doped with fixed amount of Li+, Ta5+ and Sb5+ dopants in order to enhance the piezoelectric properties. The samples then sintered at 1130 ºC for 2 hours. The XRD analysis represents that the peak of orthorhombic-tetragonal phase KNN reversed become become orthorhombic symmetric after Li+, Sb5+ and Ta5+ diffused into the KNN system. The FESEM observation shows the grain size has decrease as addition of Li+, Sb5+ and Ta5+ dopants. At 1 MHz, the dielectric behavior of KNN-LTS show increasing dielectric permittivity (ɛr = 2222.48) and lower tan δ (1.07). This sample also shows high piezoelectric charge constant (d33 = 194 pC/N) and electromechanical coupling coefficient (kp = 0.3817). In Stage 3, KNN-LTS were doped with various amount of Sr2+ (x = 0, 0.005, 0.01, 0.02, 0.03, 0.05 and 0.10 mol%) to enhance their dielectric and piezoelectric properties. The results showed that the optimum amount of Sr2+ (0.01 mol%) at the A-site KNN-LTS contributed to the excellent dielectric and piezoelectric properties for KNN-LTS ceramics. The FESEM observation on KNN-LTS doped with 0.01 mol% of Sr2+ at the A-site shows the grain size become larger (2.0-5.0 μm) and improve the density of the sample (4.48 g/ cm3). The Sr2+ doped KNN-LTS sample with 0.01 mol% of Sr2+ dopant at A-site experience the highest piezoelectric properties (d33 = 345 pC/ N and kp = 0.4835) and dielectric properties (ɛr = 3940, tan δ = 1.8). Therefore, Sr2+ doping is successfully improved the piezoelectric properties of KNN-LTS system.